Focal fibrous overgrowths: A case series and review of literature - Abhay P Kolte; Rajshri A Kolte; Tushar S Shrirao (Wolters Kluwer Medknow Publications, 2010)
Intraoral fibrous overgrowths of the soft tissues are relatively common and may be benign reactive or neoplastic lesions. A series of 10 lesions is presented which included pyogenic granuloma, fibroma and peripheral ossifying fibroma. Almost all the lesions occurred in the second and third decades and were present in the anterior segment of the jaws, with a distinct female predilection. Majority of these lesions were asymptomatic and the patients reported for treatment only due to the discomfort during function. Histopathologic examinations were done for diagnosis of these lesions. Surgical excision along with removal of causative irritants remains the treatment of choice. The extent of excision should depend on the severity of the lesion, as some of these lesions have a tendency for recurrence. All the patients in this series were closely followed up for a period of 2 years and showed no signs of recurrence.